Bioassay the Composition of the Organic Pot as a Container Media for Balsa (Ocrhoma bicolor Rowlee) Growth in Nursery - Al Muzahiq, Hizbullah; Budi, Sri Wilarso; Wulandari, Arum Sekar (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Forestry plant seedling production uses non-eco-friendly polybags. Organic pots are a solution that can be applied. This research aimed to analyze the composition and size of raw materials in organic pots for balsa growth and to examine the composition of raw materials in organic pots appropriate for balsa growth. This study used a factorial complete randomized design (CRD). There are two factors: the organic pot composition factor (A) and the mesh size factor (M). The observed parameters included the C/N ratio of organic pots, height, diameter, biomass, and plant chlorophyll content. The results showed that the highest percentage decrease in the C/N ratio was found in the A3M2 treatment. The highest average value of balsa plant growth was found in the A3M2 treatment (15% newspaper, 80% goat manure, 5% cocopeat, and ten mesh material size). The highest chlorophyll content was found in A3M1 treatments (15% newspaper, 80% goat manure, 5%cocopeat, five mesh material size). Organic pots with low C/N ratio values had higher average increases in height and diameter of plants compared to organic pots with high C/N ratio values. The optimal composition of the organic pot in this study was the A3M2 treatment.